ISOLATION AND IDENTIFICATION OF BIOFILM PRODUCING ENTEROCOCCUS FAECALIS FROM ROOT CANAL - A. M. Salih,; G. M. S. Al-Quraishi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to one of the most prevalent causes for endodontic treatment failure is the presence of Enterococcus faecalis bacterium within teeth root canals. To achieve successful treatment, it is so important to study E. faecalis behavior. The aim of study was to investigate biofilm production and antibiotic sensitivity of E. faecalis isolated from root canals. Results showed isolation of E. feacalis (65%) of samples, identified by specific gene by PCR technique. Most isolates were sensitive to Imipenem and resistant to Erythromycin, Clindamycin, Tetracycline and Trimethoprim. Strong biofilm production was detected among 29.5% of highest antibiotic resistant isolates. The results may indicate that infected root canals with E. feacalis may lead to serious complication for patients.